Use of Plackett-Burman design for rapid screening of nitrogen and carbon sources for the production of lipase in solid state fermentation by Yarrowia lipolytica from mustard oil cake (Brassica napus) - Imandi,Sarat Babu (2013)
Mustard oil cake (Brassica napus), the residue obtained after extraction of mustard oil from mustard oil seeds, was investigated for the production of lipase under solid state fermentation (SSF) using the marine yeast Yarrowia lipolytica NCIM 3589. Process parameters such as incubation time, biomass concentration, initial moisture content, carbon source concentration and nitrogen source concentration of the medium were optimized. Screening of ten nitrogen and five carbon sources has been accomplished with the help of Plackett-Burman design. The highest lipase activity of 57.89 units per gram of dry fermented substrate (U/gds) was observed with the substrate of mustard oil cake in four days of fermentation.